Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.2527/1997.75123174x
|View full text |Cite
|
Sign up to set email alerts
|

Phytase supplementation of low-phosphorus growing-finishing pig diets improves performance, phosphorus digestibility, and bone mineralization and reduces phosphorus excretion.

Abstract: Two experiments using 413 crossbred growing-finishing pigs were conducted to assess the use of a commercial microbial phytase (Natuphos) in corn-soybean meal diets to improve phytate P bioavailability and thus reduce inorganic P supplementation and fecal P excretion. In Exp. 1 (n = 189), the following diets were used: 1) .50/.40% total P, respectively, for grower and finisher phases, and no phytase; 2) .40/.35% P and no phytase; 3) diet 2 plus 250 U phytase/kg; and 4) diet 2 plus 500 U phytase/ kg. The total C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
93
5
11

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(143 citation statements)
references
References 18 publications
33
93
5
11
Order By: Relevance
“…The results of experiments studying the effect of phytase on Ca digestibility in pigs are controversial. Some reports showed no effect (Yi et al, 1996;Harper et al, 1997;Sands et al, 2001) while others showed that phytase increased both ileal (Traylor et al, 2001) and total tract (Kemme et al, 1997) Ca digestibility. There are even studies demonstrating a greater effect of added phytase on Ca digestibility than on P digestibility (Johnston et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results of experiments studying the effect of phytase on Ca digestibility in pigs are controversial. Some reports showed no effect (Yi et al, 1996;Harper et al, 1997;Sands et al, 2001) while others showed that phytase increased both ileal (Traylor et al, 2001) and total tract (Kemme et al, 1997) Ca digestibility. There are even studies demonstrating a greater effect of added phytase on Ca digestibility than on P digestibility (Johnston et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Jongbloed et al (1996a) the Ca:tP ratio ranged from 1.94:1 to 2.5:1. Harper et al (1997) in a study with growing-finishing pigs utilized three levels of P and maintained a Ca:tP ratio of approximately 1.2:1 to 1.4:1 in all diets. They reported that 500 U of microbial phytase releases 0.96 g of P per kilogram of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to determine the P equivalency value of phytase in pigs (Jongbloed et al, 1996a;Kornegay and Qian, 1996;Yi et al, 1996;Harper et al, 1997). The range of equivalency values for 500 U/kg phytase is larger ranging from 0.64 g P to 2.47 g P. Factors which may influence these equivalency value estimates include: the basal level of P, the age of the animal, the response criteria used, and perhaps most importantly the ratio of Ca to P. Qian et al (1996) reported a detrimental effect of a widening Ca:tP ratio in excess of 1.2:1 on phytase efficacy in pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally accepted that active phytase preparations can reduce faecal P excretion into the environment by improvement of phytic-P bioavailability [8,14,15,31,34]. The AFP included in the diet at a level of 500 U/kg strongly increased the P digestibility of growing pigs by 22 [40].…”
Section: Introductionmentioning
confidence: 99%